A computationally inexpensive CFD approach for small-scale biomass burners equipped with enhanced air staging. (1st May 2016) - Buchmayr, M.; Gruber, J.; Hargassner, M.; Hochenauer, C.
Highlights: Time efficient CFD model to predict biomass boiler performance. Boundary conditions for numerical modeling are provided by measurements. Tars in the product from primary combustion was considered. Simulation results were validated by experiments on a real-scale reactor. Very good accordance between experimental and simulation results. Abstract: Computational Fluid Dynamics (CFD) is an upcoming technique for optimization and as a part of the design process of biomass combustion systems. An accurate simulation of biomass combustion can only be provided with high computational effort so far. This work presents an accurate, time efficient CFD approach for small-scale biomass combustion systems equipped with enhanced air staging. The model can handle the high amount of biomass tars in the primary combustion product at very low primary air ratios. Gas-phase combustion in the freeboard was performed by the Steady Flamelet Model (SFM) together with a detailed heptane combustion mechanism. The advantage of the SFM is that complex combustion chemistry can be taken into account at low computational effort because only two additional transport equations have to be solved to describe the chemistry in the reacting flow. Boundary conditions for primary combustion product composition were obtained from the fuel bed by experiments. The fuel bed data were used as fuel inlet boundary condition for the gas-phase combustion model. The numerical and experimental investigations were performed for different operating conditions and varying wood-chip moisture on a special designed real-scale reactor. The numerical predictions were validated with experimental results and a very good agreement was found. With the presented approach accurate results can be provided within 24 h using a standard Central Processing Unit (CPU) consisting of six cores. Case studies e.g. for combustion geometry improvement can be realized effectively due to the short calculation time of the presented model. The current work provides a powerful tool for small-scale biomass boiler research and development with a perfect trade-off between quality in predicting physical trends and low computational running time.